Preparation, amino acid composition, and in Vitro antioxidant activity of okra seed meal protein hydrolysates. Issue 6 (2nd April 2021) - Yao, Hongliang; Yang, Jiani; Zhan, Jiajia; Lu, Qu; Su, Min; Jiang, Yaojiong
Abstract: To improve the utilization of okra seed, acidic and enzymatic hydrolyses of producing protein hydrolysates were respectively optimized by orthogonal experiment and response surface methodology using the degree of hydrolysis (DH) as evaluating index. Amino acid composition and antioxidant capacity in vitro of two kinds of hydrolysates were both analyzed. The degree of acidic hydrolysis was 58.53 ± 1.92% under the following optimized condition: hydrolyzing time 40 hr, temperature 95°C, ratio of acid solution to okra seed meal (OSM) powder was 5:1 (V:W/ml:g), and hydrochloric acid concentration was 18% (W/W). The degree of enzymatic hydrolysis was 16.26 ± 0.56% under the optimized condition: hydrolyzing time 8.20 hr, ratio of buffer to OSM powder was 10:1, and enzyme dosage was 3, 100 International Units (IU) g −1 . Enzymatic hydrolysates had a fuller range of amino acids and antioxidant capacity than acidic hydrolysates. The results provide technical support for the expansion of okra seed utilization. Abstract : Acidic and enzymatic protein hydrolysates were produced from okra seed by optimized hydrolysis processes. Enzymatic protein hydrolysates provided fuller range amino acid and more antioxidant capacity than acidic protein hydrolysates from okra seed meal.